Developing decision-making support systems by operating staff of npp power units - Chyzhyk, Oleksandr (National Technical University "Kharkiv Polytechnic Institute", 2024)
Methods and approaches to the development of simulation models of NPP power units are considered. It is proposed simulation model of the NPP power unit, created on the basis of the use of an oriented algorithm to describe the technological scheme of the power unit in order to calculate the parameters and characteristics that determine the technical and economic indicators, as well as the reliable and safe operation of the power unit equipment. An automated decision-making support system developed on the basis of a simulation model is described. It is intended for the analysis of the technical and economic efficiency of the nuclear power plants operation, taking into account the indicators of reliability and safe operation of the equipment.
Keywords: nuclear power plants; power units; simulation models; support systems; technical and economic indicators; reliability